Screening of rice breeding lines for brown planthopper resistance using phenotypic and molecular methods - Kumari et al, B Kusuma (Indian Journal of Plant Protection, 2018)
One hundred and nineteen F 6 breeding lines of paddy along with resistant and susceptible checks were evaluated under feld and greenhouse conditions for brown planthopper (BPH), Nilaparvata lugens (Stal.) resistance duringKharif, 2016 at APRRI & RARS, Maruteru. Out of which, 32 breeding lines in standard seed box screening and 69 in feld screening have exhibited resistant reaction to BPH. Twenty-fve breeding lines which exhibited resistancereaction in both feld and seed box screenings along with resistant and susceptible checks were used for honeydew test and molecular screening. Among 25 breeding lines, MTU 2399-24-1-1-1 (13.67 mm2) and MTU 2465-11-3-1-1 (93.33 mm2) showed lower and higher honeydew excretion area, respectively. The molecular screening was done by using 33 SSR markers, which are linked to known BPH resistant loci. Out of 33 markers used, 20 markersexhibited polymorphism and they classified the entries into II and III clusters using NTSYS and Darwin statistical packages, respectively.